Mutation of the ATPase Domain of MutS Homolog-5 (MSH5) Reveals a Requirement for a Functional MutSγ Complex for All Crossovers in Mammalian Meiosis. Issue 6 (1st June 2019) - Milano, Carolyn R; Holloway, J Kim; Zhang, Yongwei; Jin, Bo; Smith, Cameron; Bergman, Aviv; Edelmann, Winfried; Cohen, Paula E
Abstract: During meiosis, induction of DNA double strand breaks (DSB) leads to recombination between homologous chromosomes, resulting in crossovers (CO) and non-crossovers (NCO). In the mouse, only 10% of DSBs resolve as COs, mostly through a class I pathway dependent on MutSγ (MSH4/ MSH5) and MutLγ (MLH1/MLH3), the latter representing the ultimate marker of these CO events. A second Class II CO pathway accounts for only a few COs, but is not thought to involve MutSγ/ MutLγ, and is instead dependent on MUS81-EME1. For class I events, loading of MutLγ is thought to be dependent on MutSγ, however MutSγ loads very early in prophase I at a frequency that far exceeds the final number of class I COs. Moreover, loss of MutSγ in mouse results in apoptosis before CO formation, preventing the analysis of its CO function. We generated a mutation in the ATP binding domain of Msh5 ( Msh5 GA ). While this mutation was not expected to affect MutSγ complex formation, MutSγ foci do not accumulate during prophase I. However, most spermatocytes from Msh5 GA/GA mice progress to late pachynema and beyond, considerably further than meiosis in Msh5 −/− animals. At pachynema, Msh5 GA/GA spermatocytes show persistent DSBs, incomplete homolog pairing, and fail to accumulate MutLγ. Unexpectedly, Msh5 GA/GA diakinesis-staged spermatocytes have no chiasmata at all from any CO pathway, indicating that a functional MutSγ complex is critical for all CO events regardless of their mechanism of generation.